The Influence of Growth Temperature on the Properties of AlN Films Grown by Atomic Layer Deposition - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2011)
In this work, we explored the influence of the low growth temperatures on the structural and optical properties of AlN films grown by plasma enhanced atomic layer deposition using trimethylaluminum and ammonia (NH3) plasma. Structural and optical results show that AlN films grown by self-limited plasma enhanced atomic layer deposition are polycrystalline at temperatures as low as 100 degrees C.
Keywords: NITRIDE THIN-FILMS